Low-capacity decentralized electricity systems limit the adoption of electronic appliances in rural Nepal. (June 2023) - Bharadwaj, Bishal; Subedi, Mukti Nath; Malakar, Yuwan; Ashworth, Peta
Abstract: The adoption and use of electronic appliances generally contribute to higher productivity and thus are key to ameliorate living standards of rural households. A wide range of decentralized electricity systems has been used to power remote parts of Nepal. How these systems facilitate the adoption of electronic appliances, is a question under explored in the existing energy policy literature. This study bridges this gap by comparing the electronic appliance adoption among households that use micro-hydropower and solar home systems against traditional lighting solutions and grid electricity in Nepal. Applying the two-stage least-square method to data from Nepal's population and household census of 2011, we found solar home systems do not increase the use of high-wattage electronic appliances such as televisions and fridges when compared to kerosene, but micro-hydro plants and grid electricity do. This finding indicates that low-capacity electricity sources like solar home systems appear to be limited to facilitate the adoption of high-wattage electronic appliances. It is recommended that energy access policies should look beyond providing basic access to electricity for lighting and prioritize the provisioning of electricity sources that support the use of high-wattage electricity appliances. Highlights: Estimates the effect of decentralized electricity on electronic appliance (EApp) use. DES household have significantly lower numbers of EApp compared to those connected to the grid. Solar home systems do not increase electric appliance use when compared to kerosene. Micro increases mobile and TV use but not high-wattage appliances like fridges. Policies could establish minimum capacity of DES to enable EApp use.